Silent screams behind screens: An analysis of risk factors for cyberbullying victimization and protective strategies - Wang, Kuang-Hsien (International journal of economic perspectives, 2025)
Using the official Taiwan Communication Survey Database and the propensity score matching method, this study classified 1852 adolescents as actual or potential cyberbullying victims. Findings showed males, poor performers, bystanders, and anxious individuals are at higher risk. Different types of bullying, especially cyber-behavioral bullying by acquaintances, have differing effects on self-esteem. Adolescents’ responses range from seeking help to avoidance. More cyberbullying happens with educational rather than leisure internet use, suggesting educational pressure may trigger such incidents.